تطبيق العقوبات على الجرائم الواقعة عبر وسائل التواصل الاجتماعي في القانون الكويتي - عازمي ، عبد الله مزيد (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2021)
The study discusses the application of penalties for crimes committed through social media in accordance with Kuwaiti law. The research problem is concerned with the inadequacies of Kuwaiti Law No. (63) 2015 to fight against the information technology crimes. It seems that the law pertaining to the procedural aspect in tackling these crimes is neglected, since it was based on the Criminal Procedures and Trials Law No. (17) 1960 and the amendment of such laws thereof. The importance of the study signifies that the crimes related to social media are contemporary topics, as these crimes develop with the development of technology. The research examines the concept of crimes committed through social media and the criminal responsibility of those who commit these types of crimes in Kuwait. The study also discusses the role of the Kuwaiti Government in combating crimes committed through social media in international legislation as well as that of Kuwaiti legislation. The research is based on a descriptive approach which includes describing the crimes related to social media as well as the laws and procedures in the State of Kuwait to combat these crimes. The research is also based on inductive approach; by extrapolating the laws of the legislative authority and the procedures of the Kuwaiti executive authority in combating social media crimes; extrapolating the laws to combat information technology crimes in the State of Kuwait; the supported laws and their effectiveness. The research concludes with a set of findings and recommendations, i.e. The application of the Kuwaiti audiovisual law on communication crimes should be set aside; Social media programs are considered a public place and the statutory limitations in social media crimes are different from that of traditional crimes. Among the research recommendations are there is a need for the establishment of a special department which is a subdivision of the judiciary to combat information technology crimes including social media crimes. In addition, the research recommends that some Paragraphs of the legal Articles on combating information technology crimes be amended.